Comparative analysis of acceleration gradients for chip structures with different refractive indices - Vasyliev, A.V.; Bolshov, O.O.; Svistunov, O.O.; Povrozin, A.I.; Zaitcev, V.P.; Leshchenko, V.P.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2021)
The results of numerical studies of accelerating gradients in accelerators based on dielectric chip structures with different refractive indices, excited by a titanium-sapphire laser pulse, are presented. A comparative analysis of the influence of the refractive index on the rate of acceleration of electron bunches is carried out. Promising materials for the manufacture of dielectric laser accelerators are proposed. Представлені результати чисельних досліджень прискорюючих градієнтів у прискорювачах на основі діелектричних ЧІП-структур з різними показниками заломлення, збуджуваних титан-сапфіровим лазерним імпульсом. Проведено порівняльний аналіз впливу показника заломлення на темп прискорення електронних згустків. Запропоновано перспективні матеріали для виготовлення діелектричних лазерних прискорювачів. Представлены результаты численных исследований ускоряющих градиентов в ускорителях на основе диэлектрических ЧИП-структур с различными показателями преломления, возбуждаемых титан-сапфировым лазерным импульсом. Проведен сравнительный анализ влияния показателя преломления на темп ускорения электронных сгустков. Предложены перспективные материалы для изготовления диэлектрических лазерных ускорителей.